Correlates of participation in a pediatric primary care-based obesity prevention intervention - Taveras, Elsie M. (2010)
The purpose of this study was to examine correlates of participation in a childhood obesity prevention trial. We sampled parents of children recruited to participate in a randomized controlled trial. Eligible children were 2.0 - 6.9 years with BMI ≥ 95(th) percentile or 85(th)-<95(th) percentile if at least one parent was overweight. We attempted contact with parents of children who were potentially eligible. We recruited 475 parents via telephone following an introductory letter. We also interviewed 329 parents who refused participation. Parents who refused participation (n=329) did not differ from those who participated (n=475) by number of children at home (OR 0.94 per child; 95% CI: 0.77, 1.15) or by child age (OR 1.07 per year; 95% CI: 0.95, 1.20) or sex (OR 1.06 for females v. males; 95% CI: 0.80, 1.41). After multivariate adjustment, parents who were college graduates v. < college graduates were less likely to participate (OR 0.62; 95% CI: 0.46, 0.83). In addition, parents were less likely (OR 0.41; 95% CI: 0.31, 0.56) to participate if their child was overweight v. obese. Among the 115 refusers with obese children, 21% cited as a reason for refusal that their children did not have a weight problem, v. 30% among the 214 refusers with overweight children. In conclusion, parents of preschool-age children with a BMI 85-95(th)%ile are less likely to have their children participate in an obesity prevention trial than parents of children with BMI >95(th)%ile. One reason appears to be they less frequently consider their children to have a weight problem.